2021
DOI: 10.32866/001c.24389
|View full text |Cite
|
Sign up to set email alerts
|

How are Attitudes Toward COVID-19 Associated with Traveler Behavior During the Pandemic?

Abstract: This article uses data from the first wave of the COVID Future Panel study to evaluate attitudes towards COVID-19 and their influence on traveler behaviors. An exploratory factor analysis identified two underlying constructs based on the measured attitudes, namely "Concern about Pandemic Response" and "COVID Health Concern." A cluster analysis based on the factor scores yielded four groups with distinct attitudes. Those primarily concerned about the pandemic response traveled the most using private vehicles, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The percentage of respondents indicating that they have a disability is very small (only 2% indicate that they cannot drive a vehicle); consequently, within the context of this study, disability status is unlikely to be a statistically significant explanatory variable (because of the very small sample size of individuals with disabilities). However, it should be recognized that those with disabilities experience diminished quality of life, well-being, and satisfaction with daily activity-travel patterns ( 14 ).…”
Section: Data Descriptionmentioning
confidence: 99%
“…The percentage of respondents indicating that they have a disability is very small (only 2% indicate that they cannot drive a vehicle); consequently, within the context of this study, disability status is unlikely to be a statistically significant explanatory variable (because of the very small sample size of individuals with disabilities). However, it should be recognized that those with disabilities experience diminished quality of life, well-being, and satisfaction with daily activity-travel patterns ( 14 ).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Various empirical studies have examined the effects of the COVID-19 pandemic on travel preferences and behaviour. Empirical research has found substantial changes in travel frequency and trip purpose during the pandemic ( Capasso da Silva et al, 2021 , De Haas et al, 2020 , Kar et al, 2021 , Salon et al, 2021 ). Specifically, trip frequency and distances travelled decreased, mostly due to travel restrictions such as lockdown and stay-at-home orders in most countries.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found a significant drop in public transport ridership and an increase in private automobile and active transport mode use ( Abdullah et al, 2021 , De Haas et al, 2020 , Salon et al, 2021 , Shamshiripour et al, 2020 ), where sometimes a car is purchased especially to replace public transport trips ( van Hagen et al, 2021 ). Unlike changes in travel distance, trip frequency, and trip purpose which are likely introduced by travel restrictions (e.g., lockdown), a mode switch and increased WFH levels are likely due to health concerns and fears of infection as sharing space with other people can be perceived as unsafe during this time ( Capasso da Silva et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Following the pandemic, attitudes reflecting a transit-oriented lifestyle and discomfort around strangers are likely to have altered significantly. Future research is needed to explore the stability of attitudes and behaviors in a post-pandemic world, particularly in the context of emerging transportation technologies and their potential implications on the transportation system (34)(35)(36)(37)(38). On a related subject, one might question the relevance of the latent constructs considered in this study, given that only three latent variables were investigated from a wide range of alternatives.…”
Section: Study Implications and Conclusionmentioning
confidence: 99%